External challenges of development studies programmes in contributing to the development of Uganda. - Lubaale, Grace (Ideal Journal of Education and Policy Studies, 2015)
This study which ventures into the Challenges of Development Studies Programmes (DSP) in Contributing to the Development of Uganda attempted to unravel and establish the specific challenges of Development Studies Programmes offered at Uganda Martyrs University (UMU) and Makerere University Kampala (MUK). Both qualitative and quantitative approaches were employed so as to provide the necessary triangulation for getting a more composite data to articulate better the findings. Further, a descriptive research design specifically a case study was adopted in order to secure in-depth data regarding challenges of DSP offered at UMU and MUK in contributing to the development of Uganda. The study used a sample size of 260 respondents using research instruments of a semi-structured questionnaire, interview guide, and check list. The study established challenges as; Unemployment, corruption, poverty, working environments, professional body, gender and young age of graduates and finally government policies. To overcome the aforementioned challenges, the study recommends quality teaching, think tank, policy formulation and forming a professional body. It is hoped that if implemented, DSP will be able to contribute a great deal to the development process of Uganda.